2022
DOI: 10.3389/fspor.2022.938619
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence, sources and selective antecedents of organizational stressors among elite football players and coaches in the Ghana premier league: Empirical evidence for applied practice

Abstract: Globally, job-related stress has been classified as a health epidemic which is common among many individuals across diverse populations. Despite this established knowledge, research has primarily focused on the general population and among health workers. Therefore, understanding stress related experiences in the context of professional sport would help design appropriate stress management interventions for effective coping. The overarching aim of this research was to assess occupational stress related experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
2
0
1
Order By: Relevance
“…As with any validation study, it involved several research steps (e.g., sample size planning, data collection and analysis, statistical evaluation of reliability and validity). This is in line with the most recent scientific literature on the subject, i.e., [133][134][135][136], although there is a prevalence of the use of cross-sectional research designs in validation studies, i.e., [137][138][139]. It should be emphasized that cross-sectional studies make it possible to define and examine the predominance and distribution of a population phenomenon at a particular moment [136,140], whereas the validation study as a research design makes it possible to assess the psychometric characteristics of a measurement instrument [136,141].…”
Section: Methodssupporting
confidence: 86%
“…As with any validation study, it involved several research steps (e.g., sample size planning, data collection and analysis, statistical evaluation of reliability and validity). This is in line with the most recent scientific literature on the subject, i.e., [133][134][135][136], although there is a prevalence of the use of cross-sectional research designs in validation studies, i.e., [137][138][139]. It should be emphasized that cross-sectional studies make it possible to define and examine the predominance and distribution of a population phenomenon at a particular moment [136,140], whereas the validation study as a research design makes it possible to assess the psychometric characteristics of a measurement instrument [136,141].…”
Section: Methodssupporting
confidence: 86%
“…strength & conditioning coaches) is utilised (8) The study explored coaches exclusively or provided group findings separately where a sample beyond coaches (e.g. athletes or support staff ) was utilised (9) The study explored elite coaches exclusively or provided group findings separately where a heterogeneous sample (e.g. elite and non-elite) was utilised (10) The study reported on the mental health (mental wellbeing or mental ill-health) of elite-level coaches…”
Section: Search Strategymentioning
confidence: 99%
“…competition preparation and psychological state) [5,6]. On top of performance pressures, elite-level coaches also encounter multiple organisational challenges, including long working hours, job insecurity, media scrutiny and pressures to satisfy board/ management expectations [1,[6][7][8][9]. Similarly, coaches are also confronted with various personal stressors, including social isolation and relationship issues [4,6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A su vez el diseño organizacional influye sobre el potencial humano y cultura organizacional, los estudios hallaron relación entre el estado de la organización y el desempeño laboral, si el trabajador se siente seguro su trato al cliente mejora significativamente [66], [67], pero las necesidades insatisfechas también tienen relevancia, por ejemplo en jugadores profesionales se probó la efectividad de darles oportunidades de desarrollo profesional por medio de cursos becados y patrocinios [68].…”
Section: Contrastación De Las Hipótesisunclassified